Evaluation Study of Risk Management Process in The Business Process National Road Implementation Center (BPJN) West Sumatra - Detia Enda Trivilla; Akhmad Suraji; Bayu Martanto Adji (CIVED, 2025)
This study evaluates the effectiveness of risk management implementation in national road infrastructure projects managed by the National Road Implementation Agency (BPJN) of West Sumatra, Indonesia. Employing an evaluative method that integrates qualitative and quantitative approaches, this research assesses risk management practices based on the guidelines set by the Ministry of Public Works and Housing. The study utilizes document reviews, structured interviews, and perception surveys involving at least 10 respondents, including Risk Owners, Risk Managers, and officials from the Risk Management Unit (UPR) responsible for planning, financial management, and technical operations. Findings indicate that while BPJN West Sumatra has effectively implemented several risk management aspects, deficiencies persist in risk monitoring and response strategies. Notably, the study highlights the urgent need for a structured risk monitoring system, more proactive mitigation strategies, enhanced stakeholder communication, and the integration of information technology. This research contributes to the existing literature by providing a comprehensive evaluation framework for risk management effectiveness in infrastructure projects, offering practical recommendations to improve risk management capacity and support the successful execution of national road infrastructure projects in West Sumatra.